Wayfindings strategies of the cultural activities in Jonker Walk, Malacca - Normazli, Siti Huwaini; Zakariya, Khalilah (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
The research is conducted to study the wayfindings strategies of the cultural activities in Jonker Walk. Wayfindings is an object or the environmental itself that can be as landmark. Several vital issues that happen in Jonker Walk is when the tourist tend to be lost as well as be in the hard time to move from one place to another. As addition, the tourist failed to differentiate between the diverse cultural activities at Jonker Walk. The three main objectives for this study are none other than to identify the availability of the wayfindings in the Jonker Walk, to list out the diversity of the culture at the site and to understand the problem faced by the tourist and the locals related of the understanding of the culture at the site. The researcher conducts three methods which are from the qualitative and quantitative to assure the study succeed. The methods are literature review, observation and semi-structured interview. The expected outcome for this study are the proper way of implementing the wayfindings according to the guidelines outlined. To end, wayfindings can benefit everyone from any angles and perceptions as well giving good impacts to the street itself.